Products of symplectic normal matrices - de la Cruz, Ralph John (Animo Repository, 2018)
A matrix A ∈ M2n(C) is symplectic if AT 0 In −In 0 A = 0 In −In 0We show that every symplectic matrix is a product of a symplectic unitary and a symplectic skew-Hermitian matrix. We show that every symplectic matrix is a product of four symplectic skew-Hermitian matrices or a product of four symplectic Hermitian matrices. We give the possible Jordan canonical forms of symplectic matrices which can be written as a product of a symplectic Hermitian and a matrix which is either symplectic Hermitian or symplectic skew-Hermitian.